2001
DOI: 10.1902/jop.2001.72.11.1527
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Interleukin‐10 Depletion In Vivo on the Immune Response to Porphyromonas gingivalis in a Murine Model

Abstract: This study has shown that IL-10 depletion in vivo in P. gingivalis LPS-induced immune response in mice led to an elevated DTH response, an increase in serum IFN-gamma levels, and raised levels of IgG and IgG2a antibodies. Treatment with anti-IL-10 antibodies resulted in suppressed IgG1 and IgM responses and a more rapid healing of abscesses than in non-IL-10-depleted mice. These results suggest that IL-10 depletion in Pg-LPS-induced immune response in mice may lead to a Th1-like immune response and provide str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Also, IL-10 was involved in local B cell response and detected in inflamed gingival tissues [19]. IL-10 could be secreted by T cells, B cells and other periodontal cells [10, 26, 28]. Studies demonstrated that miR-146a inhibition did not change IL-10 production in human gingival fibroblasts [10].…”
Section: Discussionmentioning
confidence: 99%
“…Also, IL-10 was involved in local B cell response and detected in inflamed gingival tissues [19]. IL-10 could be secreted by T cells, B cells and other periodontal cells [10, 26, 28]. Studies demonstrated that miR-146a inhibition did not change IL-10 production in human gingival fibroblasts [10].…”
Section: Discussionmentioning
confidence: 99%
“…Together, these results indicated that the cooperative response to IL-10 and CD27/CD70 interactions appeared to regulate B-cell immunoglobulin production Nagumo and Agematsu, 1998;Agematsu et al, 1999). IL-10 is known to augment antibody production in activated B cells in some in vivo systems (Stein et al 1997;Herminajeng et al 2001;Finnegan et al 2003) as well as in some in vitro systems (Kindler and Zubler, 1997;Choe and Choi, 1998;Xu et al 2004).…”
Section: Fig 2 Continuedmentioning
confidence: 91%
“…To investigate the survival rate of the diabetic mice with LPS, Porphyromonas gingivalis LPS (3 mg/kg, LD50 = 30 mg/kg body weight)(Wako) was administered repeatedly intraperitoneally once a week to the STZ-induced diabetic mice which had shown blood glucose levels above 600 mg/dl for four months [26], [27]. The injection was conducted under inhalation anesthesia with 2% isoflurane.…”
Section: Methodsmentioning
confidence: 99%